ADAPTASI SOSIAL MAHASISWA ASING DI INSTITUT KH. ABDUL CHALIM PACET MOJOKERTO - Puji Laksono (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
The era of globalization brings the consequences of increasing the intensity of social interaction of the world community. One of them can be seen from the increase in foreign students who are studying in Indonesia. This research is about the social adaptation of foreign students at Institut KH. Abdul Chalim Mojokerto. The purpose of this research is to know how the social adaptation strategy of foreign students at Institut KH Abdul Chalim Mojokerto. This research was conducted on foreign students at Institut K.H Abdul Chalim Mojokerto. This study uses qualitative methods, ie research that relies on data from what is seen in the field or natural settings. The theory used is the social system theory of Talcott Parsons. Data collection is done by direct observation and in-depth interview. Validity of data is done by using triangulation. The results of this study indicate that foreign students have the motivation to continue their education in Indonesia. In this case, foreign students have motivation that can be categorized into two, namely the structural motivation and cultural motivation. Structural motivation, among others, is the political system and state ideology that does not support the development of Islamic culture. Cultural motivation, among others, is to learn, develop and preserve Islamic culture in their home country. Foreign students consider Indonesia as a tolerant country of difference supported by political ideology in view of religious diversity. It supports the community to develop and practice beliefs without fear of being subordinated by the community environment. Nevertheless, foreign students have difficulties in adapting to education in Indonesia, in this case, is divided into two namely the constraints of Malay and Non-Malay students. The existence of obstacles that make foreign students have a strategy in facing the existing constraints both socially and non-socially.